2017
DOI: 10.1142/s1469026817500018
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Networks for Water Body Extraction from Landsat Imagery

Abstract: Traditional machine learning methods for water body extraction need complex spectral analysis and feature selection which rely on wealth of prior knowledge. They are time-consuming and hard to satisfy our request for accuracy, automation level and a wide range of application. We present a novel deep learning framework for water body extraction from Landsat imagery considering both its spectral and spatial information. The framework is a hybrid of convolutional neural networks (CNN) and logistic regression (LR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 8 publications
0
61
0
Order By: Relevance
“…(4) The global subspaces and the local subspaces are obtained according to Equations (9-13). (5) The statistics and control limits are calculated for monitoring according to Equations (15)(16)(17)(18)(19)(20)(21). (6) Most similar mode information of faulty data is determined according to Equation (14).…”
Section: Online Mode Identification and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) The global subspaces and the local subspaces are obtained according to Equations (9-13). (5) The statistics and control limits are calculated for monitoring according to Equations (15)(16)(17)(18)(19)(20)(21). (6) Most similar mode information of faulty data is determined according to Equation (14).…”
Section: Online Mode Identification and Monitoringmentioning
confidence: 99%
“…To improve the capability of multimode process monitoring, some methods, such as multiple models methods, Gaussian mixture model, localized Fisher discriminant analysis, etc., have been developed. [15,[20][21][22][23] Multiple models methods were developed by building different monitoring models for different modes, which may be effective for each mode. [18] However, the correlations between different modes were neglected, which may cause a high false alarm rate.…”
Section: Introductionmentioning
confidence: 99%
“…For remote sensing images, the CNN and FCN have been widely applied in scene classifications [35,39], land cover classifications [40,41] and target detections [37] during recent years. Moreover, some studies have reported the application of the CNN or FCN in the surface water mapping community [29,42]. Yu et al presented a novel CNN with a logistic regression to identify water via Landsat [42].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies have reported the application of the CNN or FCN in the surface water mapping community [29,42]. Yu et al presented a novel CNN with a logistic regression to identify water via Landsat [42]. Furthermore, an FCN was proposed to map surface water by training a feature from a different land cover type [29].…”
Section: Introductionmentioning
confidence: 99%
“…The CNN approach uses convolutional windows and local connections to effectively extract the spatial information. In regard to LULC classification that is based on moderate or coarser resolution images, such as Landsat and MODIS, the CNN approach and texture features may still be advantageous in some special cases, such as cropland classifications or in the extraction of certain LULC types in special regions [21][22][23]. However, for moderate resolution LULC classification with high thematic resolution, very few researches involved neighborhood characteristics using methods like GLCM and CNN.…”
Section: Introductionmentioning
confidence: 99%